Pengaruh E-Service Quality, Product Quality, Dan Perceived Enjoyment Terhadap Repurchase Intention CGV Cinemas - Gursherine Gursherine; Vina Meliana (Research and Community Service UNIVERSITAS KALBIS, 2026)
This study aims to determine the influence of e-service quality, product quality, and perceived enjoyment on repurchase intention among users of the CGV Cinemas application. CGV is one of the digital platforms for movie ticket reservations that affects customer experience and encourages repeat purchases. This research uses a quantitative approach with purposive sampling. Data were collected using an online questionnaire distributed to 240 respondents who had purchased tickets via the CGV application in the last three months. The research instrument was tested for validity and reliability before analysis. The data analysis technique used is multiple linear regression. The results show that E-service quality has an influence on Repurchase intention. Product quality has an influence on Repurchase intention. Perceived enjoyment has an influence on Repurchase intention. These findings indicate that improving digital service quality, product quality, and user enjoyment when using the application can encourage repurchase intention. CGV is advised to improve the lowest-rated aspects to increase user loyalty.